Diagnostic Accuracy of Leucocyte Esterase Reagent Strips for Spontaneous Bacterial Peritonitis in Cirrhosis With Ascites - Salum Ali Mwinyi; Emmanuel Marcel Sindato; Emmanuel Muhimbura; Gerald Jacob Kawishe; James Joseph Yahaya (Health Science Reports, 2026)
ABSTRACT Background and Aims Spontaneous bacterial peritonitis (SBP) in patients with liver cirrhosis and ascites is a common and serious problem which is associated with high morbidity and mortality. The present study aimed to determine the diagnostic performance of the leucocyte esterase reagent strip (LERS) for the diagnosis of SBP, and we also assessed the prevalence of SBP. Methods This was a diagnostic accuracy study which was conducted at referral hospitals in Dodoma region, Tanzania, among patients with liver cirrhosis and ascites who were aged ≥ 18 years. Diagnostic performance of LERS was assessed by calculating the diagnostic accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) at three colorimetric scales (1+, 2+, and 3+) which were analyzed as separate categories. Ascitic fluid PMN count ≥ 250 cells/mm 3 was used as the reference standard, which is a pre‐specified diagnostic threshold. Results The present study included a total of 269 study subjects with a mean age of 46.2 ± 10.3 years, and the majority of the patients (61.3%, n = 165) were males. The prevalence of SBP based on the gold standard test was (19.0%, n = 51). The diagnostic performance values including, accuracy, sensitivity, specificity, PPV, and NPV of LERS using CYBOWTM series urine reagent strips were considered at colorimetric scale of 2+ as comparable to the reference standard. Under this comparable point (colorimetric scale 2+), the sensitivity, specificity, PPV, and NPV were 80.4% (95% CI = 67.6–89.8), 99.1% (95% CI = 95.7–99.9), 95.3% (95% CI = 84.2–99.4), and 95.6% (95% CI = 91.9–97.9), respectively. The diagnostic accuracy of LERS at a colorimetric scale of 2+ in this study was 96.3% (95% CI = 92.3–97.6). Conclusions This study has shown a significant proportion of SBP among the patients who were diagnosed with liver cirrhosis and had ascites. The level of diagnostic accuracy shown by LERS for SBP indicates that LERS may be used as a possible adjunctive screening tool rather than a definitive substitute for standard diagnostic assessment, especially in remote areas of resource‐limited settings where diagnostic tests like culture are still challenging.